2012
DOI: 10.1093/chromsci/bms160
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Clenbuterol at Trace Levels in Doping Analysis Using Different Gas Chromatographic–Mass Spectrometric Techniques

Abstract: This study demonstrates the development of a gas chromatography-triple quadrupole tandem mass spectrometry (GC-MS-MS) assay to detect clenbuterol in human urine and the comparison of this method with GC-MS techniques and gas chromatography-high resolution mass spectrometry (GC-HRMS) techniques. Urine samples were hydrolyzed with β-glucuronidase, extracted with methyl tert-butyl ether and dried under nitrogen. The derivative reagent was N-methyl-N-(trimethylsilyl)-trifluoroacetamide with NH4I and was analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Chemicals, including opioids, cocaine, cannabinoids, amphetamine, and agonists analysis, have been widely studied in hair and hair has proved useful in anti‐doping tests, drug‐facilitated crime evidence, postmortem toxicology, and other clinical applications . The use of hair analysis to monitoring the illegal use of β 2 agonists in both humans and livestock has also been extensively reported . Previous studies focused on investigating the residue of three β 2 agonists, clenbuterol, ractopamine, and salbutamol, in different‐colored hair, as well as in new and old hair from cattle treated with single growth‐promoting doses of these drugs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemicals, including opioids, cocaine, cannabinoids, amphetamine, and agonists analysis, have been widely studied in hair and hair has proved useful in anti‐doping tests, drug‐facilitated crime evidence, postmortem toxicology, and other clinical applications . The use of hair analysis to monitoring the illegal use of β 2 agonists in both humans and livestock has also been extensively reported . Previous studies focused on investigating the residue of three β 2 agonists, clenbuterol, ractopamine, and salbutamol, in different‐colored hair, as well as in new and old hair from cattle treated with single growth‐promoting doses of these drugs .…”
Section: Discussionmentioning
confidence: 99%
“…14 The use of hair analysis to monitoring the illegal use of β 2 agonists in both humans and livestock has also been extensively reported. 5,6,9,12,13,20,21 Previous studies focused on investigating the residue of three β 2 agonists, clenbuterol, ractopamine, and salbutamol, in different-colored hair, as well as in new and old hair from cattle treated with single growthpromoting doses of these drugs. 5,6,9,12,13 A study of cattle treated with growth-promoting doses of either ractopamine or salbutamol for 21 days found that the residues of ractopamine and salbutamol in red hair on Day 70 of withdrawal were 232.55 ng/g and 33.36 ng/g, respectively, which were higher than those recorded in white hair, indicating a significant color.…”
Section: Discussionmentioning
confidence: 99%
“…In this case those compounds were distinguished by GC-HRMS since minimal mass resolution of 5000 was required [104]. Determination of another performance enhancing drug clenbuterol in urine by GC-MS, GC-MS/MS, and GC-HRMS was studied by Yang et al GC-MS and GC-HRMS provided LODs <2 ng/mL, but the best sensitivity was achieved by GC-MS/MS (LOD 0.03 ng/mL), which represents two times lower LOD in comparison with GC-HRMS (LOD 0.06 ng/mL) [105].…”
Section: Hormones and Doping Controlmentioning
confidence: 99%
“…However, various strategies including derivatization, high resolution and/or tandem mass spectrometry allowed for the analysis at sub-ng/ mL levels as recently summarized in a study by Yang et al [78] Urine samples were enzymatically hydrolyzed, liquid-liquid extracted, and the residue was trimethylsilylated with in situ generated trimethyliodosilane to yield clenbuterol-bis-TMS. Initially, meeting the minimum required performance levels (MRPLs) and detection limits required for efficient clenbuterol testing was a complex task due to the comparably poor GC-MS properties of the analyte.…”
Section: Other Anabolic Agentsmentioning
confidence: 99%